Macrophage targeted graphene oxide nanosystem synergize antibiotic killing and host immune defense for Tuberculosis Therapy - Jiang Pi; Dongsheng Chen; Jiajun Wang; Enzhuo Yang; Jiayi Yang; Yilin Liu; Jiaqi Yu; Jiaojiao Xia; Xueqin Huang; Lingming Chen; Yongdui Ruan; Jun-Fa Xu; et al. (Elsevier, 2024)
Tuberculosis (TB), a deadly disease caused by Mycobacterium tuberculosis (Mtb) infection, remains one of the top killers among infectious diseases worldwide. How to increase targeting effects of current anti-TB chemotherapeutics and enhance anti-TB immunological responses remains a big challenge in TB and drug-resistant TB treatment. Here, mannose functionalized and polyetherimide protected graphene oxide system (GO-PEI-MAN) was designed for macrophage-targeted antibiotic (rifampicin) and autophagy inducer (carbamazepine) delivery to achieve more effective Mtb killings by combining targeted drug killing and host immunological clearance. GO-PEI-MAN system demonstrated selective uptake by in vitro macrophages and ex vivo macrophages from macaques. The endocytosed GO-PEI-MAN system would be transported into lysosomes, where the drug loaded Rif@Car@GO-PEI-MAN system would undergo accelerated drug release in acidic lysosomal conditions. Rif@Car@GO-PEI-MAN could significantly promote autophagy and apoptosis in Mtb infected macrophages, as well as induce anti-bacterial M1 polarization of Mtb infected macrophages to increase anti-bacterial IFN-γ and nitric oxide production. Collectively, Rif@Car@GO-PEI-MAN demonstrated effectively enhanced intracellular Mtb killing effects than rifampicin, carbamazepine or GO-PEI-MAN alone in Mtb infected macrophages, and could significantly reduce mycobacterial burdens in the lung of infected mice with alleviated pathology and inflammation without systemic toxicity. This macrophage targeted nanosystem synergizing increased drug killing efficiency and enhanced host immunological defense may be served as more effective therapeutics against TB and drug-resistant TB.